The art and science of ultrawideband antennas - Schantz, Hans (Artech House, 2015)
Includes numerous new problem sets and worked examples, this comprehensive treatment of ultrawideband (UWB) antennas and time-domain microwave engineering serves as an invaluable practical reference for anyone involved in antenna and RF design work. -- Edited summary from book.
Keywords: Ultra-wideband antennas.; elektronické knihy; electronic books